Steady-state analysis of an unbiased equation error adaptive IIR notch filter - Punchalard, R.; Lorsawatsiri, A.; Loetwassana, W.; Koseeyaporn, J.; Wardkein, P.; Roeksabutr, A. (My University, 2007)
This paper presents the steady-state analysis of the unbiased equation error adaptive IIR notch filter (UEANF). The difference equation for the convergence in the mean and the steady-state estimation bias is derived in closed forms. In addition, the simulation results are provided to confirm the theoretical analysis. Finally, the comparisons among the UEANF, the equation error adaptive IIR notch filter (EANF) and the output error adaptive IIR notch filter (ANF) based on theory as well as simulations have shown that the UEANF outperforms the ANF in its convergence rate and it provides unbiased estimate of the desired parameter as compared with the EANF and the ANF as well. ©2007 IEEE.